Micro Plant Remains Reveal the Function of Grooved Pottery Vessels From the Late Neolithic Meishan Site in Central China - Wang, Tao; Zang, Yafan; Ma, Zhikun; Yang, Jishuai; Yuan, Guangkuo; Yang, Xiaoyan (Frontiers in Earth Science, 2022)
From 6000 calendar years before present (cal BP) onward, the grooved pottery vessels occurred in the lower and middle reaches of the Yangtze River in succession. After a thousand years, it was introduced into central China and became popularized there around 4000 years ago. It has been proposed that the function of the grooved vessels was to process plant foods, replacing the previously used stone slabs and rollers in terms of ethnographic investigation, but there is a lack of solid and direct evidence although a few evidence of starches have been provided. Here we report our study on the sherds of grooved vessels from the Meishan site in central China (late Longshan and Erlitou period). The combined starch and phytolith analyses were firstly employed together to examine the residues on the sherds. Starches from geophytes, millets (Setaria italica and Panicum miliaceum), wheat (Triticum aestivum), and phytoliths from glumes and leaves of these crops plus rice (Oryza sativa), seem to suggest that the grooved pottery vessels were likely to be used to grind geophytes and dehusk grain seeds. But, incorporating the extremely low proportion of grooved vessels to entire pottery tools at the site, we hypothesize that the invention of grooved vessels may have been related to the success of rice domestication, and may have been used as tools to pound by-products of crops, leaves and husks somehow.